(untitled) (KMC Journal, 2022)
Studies on Psychological Sense of School Membership (PSSM) have been widespread globally for three decades. However, it has not been discussed in the context of Nepali schools’ education. A positive sense of belongingness to schools among the students is essential to foster their good academic achievement as well as their mental health. Furthermore, it also increases students’ motivation and peer adjustment. This study uncovers the sense of school belongingness of grade eight students in community schools in Nepal employing a descriptive survey design under quantitative research. The five points PSSM scale, a valid and widely used measurement scale, has been used to examine the students’ perceptions about their school membership. Four major concepts have emerged from the data analysis: sense of attachment with school, sense of acceptance, sense of school ownership, and sense of respect and honour. Results revealed that students lack a strong sense of membership towards their school although they have feelings of attachment with their school. While students have a strong perceived sense of school ownership, they feel of being a weaker relationship with their teachers. Therefore, the study has immediate application to create awareness about the psychological sense of school membership among students and PSSM into academic discourse so that the Ministry of Education can initiate the necessary measures for improved students’ learning.